Perjanjian Sewa Menyewa Tanah Hak Milik Tanpa Batas Waktu Antara WNI dengan WNA menurut Hukum Positif Indonesia - Reffa Rafelya; Lina Jamilah (UNISBA Press, 2022)
Abstract. An agreement is an act in which one or more persons bind themselves to one or more persons. The conditions for the validity of the agreement according to Article 1320 of the Civil Code